MENELAAH PELUANG POLITIK RATU DEWA SEBAGAI CALON WALIKOTA PALEMBANG DALAM PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 - Namira, Nys. Syaharani Namira; Namira, Nyimas Syaharani Namira; Taufik, Taufik Akhyar; Reni, Reni Apriani (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2025)
This research aims to examine Ratu Dewa's political opportunities as a candidate for mayor of Palembang in the simultaneous regional head elections to be held in 2024. This research uses a qualitative approach. Through the proximate opportunity structure and statre centered opportunity structure approaches. This research collected data through interviews and documentation. The results of this research reveal that Ratu Dewa's communication skills and love of the people provide a significant political advantage, with the media playing a role in shaping opinions and support. Responsiveness and proactivity in responding to important issues strengthen the image as a caring leader. Nonetheless, limitations in information about him and his performance still hamper support. The occurrence of opportunities that can lead to collective action through the steps taken by Ratu Dewa in restricting truck drivers from passing in Palembang City aims to improve safety while expanding his political opportunities. The main challenge is gaining support from major parties, reflecting the complexity in predicting the outcome of the election